2023
DOI: 10.3390/ijms24021336
|View full text |Cite
|
Sign up to set email alerts
|

2,3-Diphosphoglycerate and the Protective Effect of Pyruvate Kinase Deficiency against Malaria Infection—Exploring the Role of the Red Blood Cell Membrane

Abstract: Malaria remains a major world public health problem, contributing to poverty and inequality. It is urgent to find new efficacious tools with few adverse effects. Malaria has selected red blood cell (RBC) alterations linked to resistance against infection, and understanding the protective mechanisms involved may be useful for developing host-directed tools to control Plasmodium infection. Pyruvate kinase deficiency has been associated with resistance to malaria. Pyruvate kinase-deficient RBCs display an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…Earlier studies have also demonstrated that 2,3-DPG's impact on RBC deformability and membrane zeta potential was relatively minor, and these changes did not impede effective parasite re-invasion or egress. Moreover, cytotoxicity remained low, with no discernible alterations in ATP levels and no noticeable effect on the parasite when RBCs were subjected to 2,3-DPG treatment before infection [15,16]. We hypothesize that a distinct entry mechanism for exogenous 2,3-DPG in infected and non-infected RBCs may occur.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Earlier studies have also demonstrated that 2,3-DPG's impact on RBC deformability and membrane zeta potential was relatively minor, and these changes did not impede effective parasite re-invasion or egress. Moreover, cytotoxicity remained low, with no discernible alterations in ATP levels and no noticeable effect on the parasite when RBCs were subjected to 2,3-DPG treatment before infection [15,16]. We hypothesize that a distinct entry mechanism for exogenous 2,3-DPG in infected and non-infected RBCs may occur.…”
Section: Discussionmentioning
confidence: 86%
“…Previous results showed that addition of 2,3-DPG to an in vitro P. falciparum culture medium significantly impaired the parasite's intraerythrocytic developmental cycle (IDC), the metabolic profile of 2,3-DPG-treated infected cells became more similar to that of non-infected cells, and host cells were not significantly affected. Also, parasites exposed to 2,3-DPG produced significantly fewer progeny, independently of the ATP level inside the cell [15,16]. Therefore, to confirm these preliminary results and understand the biological processes involved in this response, in this study, we analyzed the differential gene expression and the transcriptomic profile of schizogonic P. falciparum trophozoites from in vitro cultures subjected or not subjected to the action of 2,3-DPG, using Nanopore Sequencing Technology.…”
Section: Introductionmentioning
confidence: 72%
“…Infections caused by the protozoa Plasmodium falciparum and Trypanosoma cruzi , the causative agents of malaria and Chagas disease, were also the subject of two papers. Carvalho and co-authors [ 9 ] investigated the association between pyruvate kinase deficiency and resistance to malaria. The authors used atomic force microscopy and other experimental approaches to investigate modifications of red blood cell morphology, membranes, and biomechanical properties on in vitro cultures of Plasmodium falciparum treated with 2,3-diphosphoglycerate [ 9 ].…”
mentioning
confidence: 99%
“…Carvalho and co-authors [ 9 ] investigated the association between pyruvate kinase deficiency and resistance to malaria. The authors used atomic force microscopy and other experimental approaches to investigate modifications of red blood cell morphology, membranes, and biomechanical properties on in vitro cultures of Plasmodium falciparum treated with 2,3-diphosphoglycerate [ 9 ]. The results indicate that 2,3-diphosphoglycerate has only a mild effect on red blood cells when compared with the presence of the parasite on the host cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation